1952
DOI: 10.1038/icb.1952.53
|View full text |Cite
|
Sign up to set email alerts
|

Serological Studies of the Multiplication of a Staphylococcal Bacteriophage

Abstract: In a previous paper (Rountree, 1951a) it was reported that complement fixation occurred wben coli bacteriophase T5 reacted with its homologous antiserum in the presence of complement. By cyanide lysis during the latent period. T5 infected cells were shown to synthesize antigenic material reacting iu tin* fomplcnient fixation test at a stage in the phage growtli cycle at which few or no infective phage particles could be demonstrated. It was postulated that the final step in phage multiplication, i.e. the prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

1954
1954
1965
1965

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 1 publication
1
9
0
2
Order By: Relevance
“…There is no evidence of inhibition of fixation in excess serum (at constant antigen). Similar results have been obtained with T2:anti-T2 (Lanni and Lanni, unpublished data), but Rountree (1951Rountree ( , 1952) has failed to observe antigen-excess inhibition with either phage T5 or phage 3A. (2) With serum diluted 1:800 and less so at 1:400, the curve shows an aberration at high antigen concentration due to anticomplementary effect of the antigen. At the extreme right, all curves approach basal levels set by the anticomplementary effect of serum at various dilutions.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…There is no evidence of inhibition of fixation in excess serum (at constant antigen). Similar results have been obtained with T2:anti-T2 (Lanni and Lanni, unpublished data), but Rountree (1951Rountree ( , 1952) has failed to observe antigen-excess inhibition with either phage T5 or phage 3A. (2) With serum diluted 1:800 and less so at 1:400, the curve shows an aberration at high antigen concentration due to anticomplementary effect of the antigen. At the extreme right, all curves approach basal levels set by the anticomplementary effect of serum at various dilutions.…”
Section: Resultssupporting
confidence: 64%
“…There is, therefore, no evidence of an early completion of a pool of antigen later incorporated into phage (see Rountree, 1951 figure 2 suggested that the infectivity but not the serological activity of the infecting phage is lost shortly after adsorption. Since, however, the infected cultures were lysed artificially, the experiments gave no evidence as to whether the antigen entered the host cell as suggested by Rountree (1951Rountree ( , 1952 remained outside as suggested by findings of Hershey and Chase (1952) with T2.…”
Section: [Vol 67mentioning
confidence: 93%
See 1 more Smart Citation
“…Supernatants of the broth cultures or of broth washings from the agar plates were filtered through Seitz E. K. filter pads. The serological group) of each phage was determined by methods de-scribed by Rountree (1949), using specific antisera prepared by the immunization of rabbits to phages of the serological groups A, B, F, and L;…”
Section: Methodsmentioning
confidence: 99%
“…When propagated in staphylococcus strain Pa, the two phages displayed differences in plaque size, adsorption constants in broth (Rountree, 1952), requirements of divalent cations for penetration and growth (Rountree, 1955), length of the minimum latent period and average burst size ( Table 2). Their ability to show plaques on a number of indicator strains of staphylococci is given in Table 3 and expressed as: ( a ) numbers of plaqueslml.…”
Section: Characters Of the Phages 47cipa And Collpamentioning
confidence: 99%